Amiodarone and lidocaine for shock refractory ventricular fibrillation or ventricular tachycardia in out-of-hospital cardiac arrest: are they really effective? - Sugiyama, Kazuhiro; Kashiura, Masahiro; Hamabe, Yuichi (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
In 2015, the American Heart Association and European Resuscitation Council updated the guidelines for cardiopulmonary resuscitation (CPR) and emergency cardiovascular care according to the International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science with Treatment Recommendations (1-3). The guidelines recommend administration of amiodarone for sustained ventricular fibrillation (Vf) and ventricular tachycardia (VT) refractory to CPR, defibrillation, and vasopressor in out-of-hospital cardiac arrest. Lidocaine is recommended as an alternative to amiodarone. However, these recommendations remain weak and are based on the two previous randomized controlled trials (RCTs) performed more than 10 years ago. In these trials, compared with both placebo and lidocaine, amiodarone improved the rate of return of spontaneous circulation (ROSC) but not the survival to hospital discharge and neurological outcome (4). However, these studies were not statistically powered to investigate survival and neurological outcome, so the actual efficacy of amiodarone therapy remains undetermined.